2016
DOI: 10.5194/hess-20-125-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal assessment of WRF, TRMM and in situ precipitation data in a tropical mountain environment (Cordillera Blanca, Peru)

Abstract: Abstract. The estimation of precipitation over the broad range of scales of interest for climatologists, meteorologists and hydrologists is challenging at high altitudes of tropical regions, where the spatial variability of precipitation is important while in situ measurements remain scarce largely due to operational constraints. Three different types of rainfall products -ground based (kriging interpolation), satellite derived (TRMM3B42), and atmospheric model outputs (WRF -Weather Research and Forecasting) -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 55 publications
4
56
0
Order By: Relevance
“…On a general way, all the SPEs are unsuitable over the glacial region with very low statistical scores at both monthly and daily time steps. This is related to PMW difficulties to retrieve accurate precipitation estimates over the frozen area, which appear to be similar to ice precipitation aloft in the scattering signal in microwave channels on satellites [46][47][48]. Therefore, SPEs algorithms have difficulties in distinguishing between the emission from frozen surfaces and the scattering from ice precipitation aloft.…”
Section: Discussionmentioning
confidence: 99%
“…On a general way, all the SPEs are unsuitable over the glacial region with very low statistical scores at both monthly and daily time steps. This is related to PMW difficulties to retrieve accurate precipitation estimates over the frozen area, which appear to be similar to ice precipitation aloft in the scattering signal in microwave channels on satellites [46][47][48]. Therefore, SPEs algorithms have difficulties in distinguishing between the emission from frozen surfaces and the scattering from ice precipitation aloft.…”
Section: Discussionmentioning
confidence: 99%
“…The overpredicting behaviour has been observed in other tropical areas (Mourre et al, 2016). While the details of the implementation of the WRF model are out of the scope of this study, possible causes of the precipitation error found by other authors include; errors in the lateral boundary conditions (Ochoa et al, 2014); poor representation of the topography (Ochoa et al, 2014); and choice of convective treatment, microphysics and planetary boundary layer (Jankov et al, 2005).…”
Section: Evaluating Precipitation Forecasts From the Wrf Modelmentioning
confidence: 94%
“…As for TRMM, the GPM level 2 data include many variables, but the key variable evaluated in this work is the estimated surface precipitation rate ("precipRateESurface"), although, in practice, there is little difference between this variable and the classical TRMM variable ("precipRateNearSurface"). The GPM level 2-DPR product is unlikely to be as broadly used as ground-based measurements or level 3 satellite precipitation accumulation products [26][27][28][29][30]. However, it is vitally important to the ground validation study using dense radar and gauge network (like the present study) and to the generation of the level-3 products.…”
Section: Global Precipitation Measurement Spaceborne Radar (Gpm-dpr) mentioning
confidence: 97%